2019
DOI: 10.1088/1361-6579/ab165f
|View full text |Cite
|
Sign up to set email alerts
|

The influence of resting heart rate on pulse wave velocity measurement is mediated by blood pressure and depends on aortic stiffness levels: insights from the Corinthia study

Abstract: Objective: Increased resting heart rate as well as increased arterial stiffness are both independent predictors of cardiovascular events and mortality. Results of previous studies have failed to converge concerning the association between heart rate and arterial stiffness, regardless of other potential confounders, such as age, gender and particularly blood pressure (BP). We aimed to investigate: (a) the degree of association (if any) between resting heart rate and carotid-to-femoral pulse wave velocity (PWV),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 44 publications
2
24
1
Order By: Relevance
“…The influence of heart rate on PWV measurements remains controversial, with conflicting results observed in both acute and epidemiological studies [ 30 , 31 , 32 , 33 ]. A significant blood pressure independent association between heart rate and PWV was mentioned [ 33 ], significant only for subjects with increased aortic stiffness [ 34 ]. A higher resting heart rate was independently associated with arterial stiffness in healthy Korean adults [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The influence of heart rate on PWV measurements remains controversial, with conflicting results observed in both acute and epidemiological studies [ 30 , 31 , 32 , 33 ]. A significant blood pressure independent association between heart rate and PWV was mentioned [ 33 ], significant only for subjects with increased aortic stiffness [ 34 ]. A higher resting heart rate was independently associated with arterial stiffness in healthy Korean adults [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of the RHR on PWV are still controversial, with conflicting results being observed. Some researchers in the Corinthia study suggested that the influence of the RHR on PWV is mediated by BP [41], and the product of the RHR times the BP was reported to be associated with baPWV [42]. However, approximately half of the existing epidemiological studies have reported a significant BP-independent association between the RHR and PWV [43].…”
Section: Discussionmentioning
confidence: 99%
“…The total dataset (organized in pairs of inputs and outputs) was kept for the training/testing process. The carotid-to-femoral pulse wave velocity (cfPWV) was measured in every subject as previously described [76][77][78] . In brief, cfPWV measurement was performed using the SphygmoCor apparatus (AtCor Medical Pty Ltd, West Ryde, Australia).…”
Section: Synthetic Population Generationmentioning
confidence: 99%